Development of electrostatic supercapacitors by atomic layer deposition on nanoporous anodic aluminum oxides for energy harvesting applications - Iglesias, Lucía; Vega, Víctor; García, Javier; Hernando, Blanca; Prida, Víctor M. (Frontiers in Physics, 2015)
Nanomaterials can provide innovative solutions for solving the usual energy harvesting and storage drawbacks that take place in conventional energy storage devices based on batteries or electrolytic capacitors, because they are not fully capable for attending the fast energy demands and high power densities required in many of present applications. Here, we report on the development and characterization of novel electrostatic supercapacitors made by conformal Atomic Layer Deposition on the high open surface of nanoporous anodic alumina membranes employed as templates. The structure of the designed electrostatic supercapacitor prototype consists of successive layers of Aluminium doped Zinc Oxide, as the bottom and top electrodes, together Al2O3 as the intermediate dielectric layer. The conformality of the deposited conductive and dielectric layers, together with their composition and crystalline structure have been checked by XRD and electron microscopy techniques. Impedance measurements performed for the optimized electrostatic supercapacitor device give a high capacitance value of 200 µF/cm2 at the frequency of 40 Hz, which confirms the theoretical estimations for such kind of prototypes, and the leakage current reaches values around of 1.8 mA/cm2 at 1 V. The high capacitance value achieved by the supercapacitor prototype together its small size turns these devices in outstanding candidates for using in energy harvesting and storage applications.